Fabrication and properties of magnesium-calcium alloy via powder metallurgy technique - Syaza Nabilla Dato' Mohd Suhaimi (School of Materials Engineering, 2016)
The research objectives are to fabricate the Mg-Ca alloy via powder metallurgy method; to study the effects of amount of calcium content in Mg-Ca alloy to physical and mechanical properties; to examine the corrosion rate of Mg-Ca alloy to study its biodegradability.